ANALISIS STRATEGI PENGEMBANGAN PEMASARAN INDUSTRI KECIL DAN MENENGAH KARYA UNISI DI KECAMATANTAMPAN KOTA PEKANBARU - Mar’aini Mar’aini (Ensiklopedia of Journal, 2019)
Analysis on the marketing development strategy of Small and Medium Industries produced by IKM Unisi aimed to find out the marketing strategies both market segmentation, target markets, positioning and marketing mix. It was conducted to develope an effort to anticipate threats and seize opportunities for sustainability and the survival ability of the Unisi IKM work and remain competitive and continue to develop in meeting the demands of consumers both locally and nationally. The analysis used SWOT to find out Strengths, Weaknesses, Opportunities and Threats for Unisi's IKM.The results of the study showed that the marketing strategies which were used was appropriate, but there were weaknesses in the marketing mix, especially in promotion. Unisi IKM Karya must be vigorous to promote, Public Relation sales promotions, Direct and Online marketing to get opportunities and anticipate threats. Keywords: Marketing Strategy, SWOT Analysis, Unisi IKM Work